Calculation of Weibull life expectancy parameters from fracture data using the maximum likelihood criterion and a NeIder-Mead simplex minimisation algorithm - Brauns, Etienne; Patyn, Johan (Computer Assisted Methods in Engineering and Science, 1996)
This paper describes a mathematical technique to calculate the model parameters for a classical Weibull statistic. This type of statistic can be applied in a number of life time expectancy problems. A typical example is the brittle behaviour of components produced from technical ceramics. A NeIder-Mead simplex algorithm is introduced to obtain the Weibull parameters using the maximum likelihood criterion . Program code for a Matlab for Windows environment is presented.